Myostatin blockade with a fully human monoclonal antibody induces muscle hypertrophy and reverses muscle atrophy in young and aged mice. Issue 1 (December 2015) - Latres, Esther; Pangilinan, Jeffrey; Miloscio, Lawrence; Bauerlein, Roy; Na, Erqian; Potocky, Terra; Huang, Ying; Eckersdorff, Mark; Rafique, Ashique; Mastaitis, Jason; Lin, Calvin; Murphy, Andrew; et al.
Abstract Background Loss of skeletal muscle mass and function in humans is associated with significant morbidity and mortality. The role of myostatin as a key negative regulator of skeletal muscle mass and function has supported the concept that inactivation of myostatin could be a useful approach for treating muscle wasting diseases. Methods We generated a myostatin monoclonal blocking antibody (REGN1033) and characterized its effects in vitro using surface plasmon resonance biacore and cell-based Smad2/3 signaling assays. REGN1033 was tested in mice for the ability to induce skeletal muscle hypertrophy and prevent atrophy induced by immobilization, hindlimb suspension, or dexamethasone. The effect of REGN1033 on exercise training was tested in aged mice. Messenger RNA sequencing, immunohistochemistry, and ex vivo force measurements were performed on skeletal muscle samples from REGN1033-treated mice. Results The human monoclonal antibody REGN1033 is a specific and potent myostatin antagonist. Chronic treatment of mice with REGN1033 increased muscle fiber size, muscle mass, and force production. REGN1033 prevented the loss of muscle mass induced by immobilization, glucocorticoid treatment, or hindlimb unweighting and increased the gain of muscle mass during recovery from pre-existing atrophy. In aged mice, REGN1033 increased muscle mass and strength and improved physical performance during treadmill exercise. Conclusions We show that specific myostatin antagonism with the human antibody REGN1033 enhanced muscle mass and function in young and aged mice and had beneficial effects in models of skeletal muscle atrophy.